Pelaksanaan BUMDes Dalam Meningkatkan Pendapatan Masyarakat Dan Pendapatan Asli Desa Di Kecamatan Belo Kabupaten Bima - Hajairin Bima (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2020)
Belo District Kabupeten Bima has 9 villages, and on average already has a Village-Owned Enterprises (BUMDes). The existence of BUMDes is one of the mandates in Law Number 6 of 2014 concerning Villages that deliver Villages as the center of Indonesian people's lives aspired by the Constitution. While the management of BUMDes in Belo District did not run optimally, out of 9 villages there were 3 villages that had new Village Regulations on BUMDes, besides that they still used the AD / ART as management standards for their BUMDes. While the presence of BUMDes in the aspect of improving the community's economy and increasing Village Original Income (PADesa) in Belo District, Bima Regency, has not yet had a positive impact on economic improvement and PADesa. Then the role of the community is still very weak, this is caused by the view that the granting of loans by BUMDes is considered as state money that does not need to be returned, this is still an obstacle in managing BUMDes in Belo District, Bima Regency.